Empirical Evidence on Recent Trends in Pro Forma Reporting - BHATTACHARYA, Nilabhra (Institutional Knowledge at Singapore Management University, 2004)
This study provides descriptive evidence on the controversial trend adopted by many firms in recent years of reporting earnings figures on a pro forma basis. pro forma earnings exclude normal income statement items that managers deem to be nonrecurring or nonrepresentative of ongoing operations. We examine a large sample of actual pro forma press releases issued between January 1998 and December 2000. We find that pro forma announcers tend to be relatively “young” firms that are concentrated primarily in the tech sector and business services industries, and that they are significantly less profitable, more liquid, and have higher debt levels, P‐E ratios, and book‐to‐market ratios than other firms in their own industries. Our results indicate that while firms commonly exclude multiple expenses in arriving at their pro forma earnings figure, they usually do not exclude the same items in subsequent pro forma announcements. These results support the criticism that pro forma announcements are often motivated by managers' desires to meet or beat analysts' expectations or to avoid earnings decreases.